Transnational creative activism : writing activism poetry in response to an international human rights crisis ; &, Border walker poetry collection : a thesis and poetry collection presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Creative Writing at Massey University, Albany . EMBARGOED until at least 17 Nov 2025. - Geers, April-Rose (Massey University, 2022)
In this thesis, I explore, analyse, and demonstrate creative writing, and more specifically poetry, as a means of transnational creative activism. In my critical essays, I discuss key practices and principles of creative activism, as a scholarly field, and expand definitions to encompass activism poetry and short stories, focussing specifically on writing that crosses spaces. In my poetry collection Border Walker, I navigate barriers of geography, culture, language, and religion to connect with followers of the Bahá’í Faith suffering persecution in Iran and to take action for their cause. My understanding of transnational activism poetry relies on notions of: imagination and participation, as developed from advancements in creative activism scholarship and reader-response theory; empathy and intimacy, as an intervention in current developments in affect theory; and lyricism and reflexivity, as a means of finding a position from which to speak. In my poetry and my essays, I reflect on my position as an Aotearoa New Zealand woman poet writing about a people and culture once foreign to me, and engage with the ethical issues and potential consequences of my work. This thesis is practice-as-research with publications and was conducted with approval of the Massey University Human Ethics Northern Committee. The weighting is 50% critical essays, comprising a theoretical framework, literary analysis, exegesis, and craft exposition; and 50% creative, in the form of a poetry collection.
Keywords: Poetry; Creative writing; Political aspects; Human rights in literature; Transnationalism in literature; New Zealand poetry; 21st century; 360201 Creative writing (incl. scriptwriting); 470599 Literary studies not elsewhere classified